2021
DOI: 10.3390/ph14010039
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of Multiple Doses of pDNA Vaccines against SARS-CoV-2

Abstract: Since its identification in Wuhan, China, in December 2019, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the causative agent of coronavirus disease 2019 (COVID-19), has resulted in 46 million cases and more than one million deaths worldwide, as of 30 October 2020. Limited data exist on the magnitude and durability of antibodies generated by natural infection with SARS-CoV-2 and whether they can provide long-lasting immunity from reinfection. Vaccination has proven the most effective measure fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Previous studies on DNA vaccines have determined that the number of doses required for effective vaccination is dependent on the antigen and virus types and how they interact with the immune system. 25 One to two doses of the DNA vaccine are enough to elicit sufficient neutralising antibody responses to the influenza virus, whereas three to four doses are needed to produce protective humoral responses against HIV. 26 In a preclinical study on a plasmid DNA vaccine for SARS-CoV-2, the magnitude of binding and neutralising antibody responses was the highest after three doses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on DNA vaccines have determined that the number of doses required for effective vaccination is dependent on the antigen and virus types and how they interact with the immune system. 25 One to two doses of the DNA vaccine are enough to elicit sufficient neutralising antibody responses to the influenza virus, whereas three to four doses are needed to produce protective humoral responses against HIV. 26 In a preclinical study on a plasmid DNA vaccine for SARS-CoV-2, the magnitude of binding and neutralising antibody responses was the highest after three doses.…”
Section: Discussionmentioning
confidence: 99%
“… 26 In a preclinical study on a plasmid DNA vaccine for SARS-CoV-2, the magnitude of binding and neutralising antibody responses was the highest after three doses. 25 Future studies on humoral immunogenicity after another booster dose of GX-19N are required.…”
Section: Discussionmentioning
confidence: 99%
“…Health care professionals can create awareness among general public regarding Covid-19 vaccination also clarify their doubts on Covid-19 vaccination. We can save our community and the whole world from Covid-19 pandemic through vaccination [1][2][3][4][5][6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on DNA vaccines have determined that the number of doses required for effective vaccination is dependent on the antigen and virus types and how they interact with the immune system. 22 One to two doses of the DNA vaccine are enough for eliciting sufficient neutralizing antibody responses to influenza virus, whereas three to four doses are needed to produce protective humoral responses against HIV. 23 In a preclinical study of a plasmid DNA vaccine for SARS-CoV-2, it was reported that the magnitude of binding and neutralizing antibody responses was the highest after three doses.…”
Section: Discussionmentioning
confidence: 99%
“…23 In a preclinical study of a plasmid DNA vaccine for SARS-CoV-2, it was reported that the magnitude of binding and neutralizing antibody responses was the highest after three doses. 22 Further studies on humoral immunogenicity after another booster dose of GX-19N should be considered.…”
Section: Discussionmentioning
confidence: 99%